Comparing wage levels and developments in Europe: Mind the data source - Joris Schröder; Monika Schwarzhappel (The Vienna Institute for International Economic Studies (wiiw), 2020)
Wages directly affect the wellbeing and living conditions of the working population, household consumption and domestic demand, but also a country's competitiveness. However, methodological differences across multiple data sources mean that it is a complex matter to make an accurate assessment of wage levels, their developments and differentials across European countries. Consequently, this paper seeks to compare the available data sources regarding coverage, concepts and the measurements used. First, we look at the most frequently used data sources for information on individual wages (national accounts data, Labour Cost Survey, Structure of Earnings Survey and administrative data) in terms of coverage, the various definitions applied (labour cost, compensation, wages and salaries, gross earnings) and measurement issues (employees, full-time equivalents (FTEs)). To underpin this research, a comprehensive database has been set up, encompassing data from these sources. In this report, we present selected results to illustrate how a comparison of data sources and concepts regarding wage developments can improve our assessment of wage levels and wage developments across European countries. These results also provide some insight into the impact of applying various conversion rates (exchange rates, purchasing power parity (PPP), price deflators such as the Consumer Price Index (CPI)) to wage data.
Keywords: J30; J31; C82; C83; 330; labour cost; compensation; wages and salaries; earnings; living conditions; competitiveness